1999
DOI: 10.1021/jp990444l
|View full text |Cite
|
Sign up to set email alerts
|

Stable Dimerized Alkoxy Species of 2-Methylpropene on Mordenite Zeolite Studied by FT-IR

Abstract: Adsorption and reactions of 2-methylpropene (isobutene) on mordenite were investigated between 150 and 300 K by infrared (IR) spectroscopy. The methyl groups of isobutene interacted with the acidic OH groups of mordenite below 160 K, which was converted to the strongly interacted π-bonded isobutene to the acidic OH groups (π-complex). Above 200 K, the π-bonded isobutene dimerized even under evacuation condition. The stable 2,4,4-trimethyl-2-pentoxy species was identified by FT-IR by comparison with the spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 32 publications
2
70
0
5
Order By: Relevance
“…Isobutene formed on zeolite acid sites is unstable, suggesting that the π-bonded isobutene on the acid sites of zeolite is dimerized, resulting in 2,4,4-trimethyl-2-pentoxy formed via 2,2,4-trimethyl-1-pentene and 2,2,4-trimethyl-2-pentene 35) . Therefore, dimerization and oligomerization of isobutene tend to proceed over zeolites with higher acidity.…”
Section: Formation Of Carbonaceous Species On H-beta Zeolitesmentioning
confidence: 99%
“…Isobutene formed on zeolite acid sites is unstable, suggesting that the π-bonded isobutene on the acid sites of zeolite is dimerized, resulting in 2,4,4-trimethyl-2-pentoxy formed via 2,2,4-trimethyl-1-pentene and 2,2,4-trimethyl-2-pentene 35) . Therefore, dimerization and oligomerization of isobutene tend to proceed over zeolites with higher acidity.…”
Section: Formation Of Carbonaceous Species On H-beta Zeolitesmentioning
confidence: 99%
“…It is, however, about 26 kJ mol À1 less stable than the adsorption p complex of isobutene with the Brønsted site. Nevertheless, all experimental attempts [13,14] to produce evidence for either the tertbutyl cation or an alkoxide have been unsuccessful so far, and the existence of tert-butyl cations in zeolites remains controversial.Herein we report density functional theory (DFT) calculations for the reaction of isobutene with H-ferrierite (H-FER, 1) with formation of the p complex 2 (Scheme 1). We applied periodic boundary conditions to a large simulation cell of dimensions 1870 1417 1496 pm 3 .…”
mentioning
confidence: 99%
“…It is, however, about 26 kJ mol À1 less stable than the adsorption p complex of isobutene with the Brønsted site. Nevertheless, all experimental attempts [13,14] to produce evidence for either the tertbutyl cation or an alkoxide have been unsuccessful so far, and the existence of tert-butyl cations in zeolites remains controversial.…”
mentioning
confidence: 99%
“…In the first sight, this is in accordance with the fact that to date no free carbenium ions are experimentally observed on the surface of acidic zeolites. [26][27][28] Moreover, Brouwer 22 found that double-bond shift occurs and follows a concerted reaction mechanism; and in situ spectroscopic studies (solid-state NMR and IR) of the interaction of Brønsted acid sites with hexene indicated that protonation of adsorbed olefins results in the formation of covalent alkoxide species.…”
Section: Introductionmentioning
confidence: 99%